2021
DOI: 10.1088/1748-9326/abfa4e
|View full text |Cite
|
Sign up to set email alerts
|

Aligning agri-environmental subsidies and environmental needs: a comparative analysis between the US and EU

Abstract: The global recognition of modern agricultural practices’ impact on the environment has fuelled policy responses to ameliorate environmental degradation in agricultural landscapes. In the US and the EU, agri-environmental subsidies (AES) promote widespread adoption of sustainable practices by compensating farmers who voluntarily implement them on working farmland. Previous studies, however, have suggested limitations of their spatial targeting, with funds not allocated towards areas of the greatest environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…The implications for ecological effectiveness are therefore indirect and strongly linked to the concept of additionality (Engel, 2016), that is whether AES lead to an actual change of practice or rather subsidize a practice that the farmer was already implementing on their land (or, at least, was already considering to implement). Furthermore, the spatial placement of AES plays an important role in determining their ecological effectiveness—while on marginal land, they may entail the lowest opportunity costs, it may well be the intensively managed, productive areas where they would make the most significant difference in terms of ecological effectiveness (see Biffi et al, 2021; Früh‐Müller et al, 2019; Paulus et al, 2022). Also, to be ecologically effective, most AES need to be adopted long‐term themselves (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The implications for ecological effectiveness are therefore indirect and strongly linked to the concept of additionality (Engel, 2016), that is whether AES lead to an actual change of practice or rather subsidize a practice that the farmer was already implementing on their land (or, at least, was already considering to implement). Furthermore, the spatial placement of AES plays an important role in determining their ecological effectiveness—while on marginal land, they may entail the lowest opportunity costs, it may well be the intensively managed, productive areas where they would make the most significant difference in terms of ecological effectiveness (see Biffi et al, 2021; Früh‐Müller et al, 2019; Paulus et al, 2022). Also, to be ecologically effective, most AES need to be adopted long‐term themselves (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…37 Subsidies based on the area farmed, as it is still the rule in the European Union or the US, make such forms of assessment completely unfeasible. 38 , 39 …”
Section: Agriculture Of Today: Specialized Vulnerable and Energy-inef...mentioning
confidence: 99%
“…In Slovenia, increased production, especially in the beef and dairy sectors, which was supported by direct payments of the common agricultural policy, and a forest succession in marginal areas have been identified as potential key factors in the recent loss of agricultural land biodiversity in Slovenia [ 45 ]. In another study, Biffi et al [ 46 ] found that higher spending on agri-environment schemes was associated with areas with low levels of soil organic carbon and high greenhouse gas emissions in both the US and the EU, with inconsistencies identified between the funding and environmental needs, namely, not targeting those areas with the highest water stress, that were threatened with biodiversity loss, soil erosion or nutrient runoff.…”
Section: Literature Reviewmentioning
confidence: 99%